How large is the compensating wage differential for R&D workers? - Arnaud Dupuy; Wendy Smits (Institute for the Study of Labor (IZA), 2009)
The aim of this paper is to measure the extent to which lower wages in R&D functions reflect a preference effect. In contrast to the bulk of the literature on compensating wage differentials that compares wage levels of jobs with different attributes, we constructed measures of willingness to accept (WTA) and pay (WTP) for an R&D jobs using contingent valuation technique. Earnings regressions using OLS show an R&D wage penalty of about 3.5%. However, hedonic OLS regressions of WTA and WTP give significant relative preference parameters for R&D jobs that range from 0.19 to 0.22.
urn:nbn:de:101:1-2009061594
Keywords: J3; 330; R&D workers; compensating wage differentials; hedonic prices; Wissenschaftler; Industrielle Forschung; Lohnstruktur; Willingness to pay; Hedonischer Preis; Niederlande